SharePoint 2003 advanced concepts : site definitions, custom templates, and global customizations - Nadrowski, Jason (Microsoft Windows server system series., 2006)
In SharePoint 2003 Advanced Concepts, two world-class SharePoint consultants show how to make SharePoint & ldquo;jump through hoops & rdquo; for you & ndash;and do exactly what you want. ¨Jason Nadrowski and Stacy Draper have built some of the most diverse SharePoint enterprise implementations. Now, drawing on their extraordinary & ldquo;in the trenches & rdquo; experience, they present solutions, techniques, and examples you simply won & rsquo;t find anywhere else. ¨SharePoint 2003 Advanced Concepts addresses every facet of SharePoint customization, from site definitions and templates to document libraries and custom properties. The authors cover both Windows SharePoint Services and SharePoint Portal Server 2003 and illuminate SharePoint & rsquo;s interactions with other technologies & ndash;helping you troubleshoot problems far more effectively. ¨Next time you encounter a tough SharePoint development challenge, don & rsquo;t waste time: get your proven solution right here, in SharePoint 2003 Advanced Concepts . ¨ÈÈÈ¨& bull;¨Construct more powerful site and list templates ÈÈÈ¨& bull;¨Control how SharePoint uses ghosted and unghosted pages ÈÈÈ¨& bull;¨Use custom site definitions to gain finer control over your site ÈÈÈ¨& bull;¨Build list definitions with custom metadata, views, and forms ÈÈÈ¨& bull;¨Troubleshoot WEBTEMP, ONET. XML, SCHEMA. XML, SharePoint databases, and their interactions ÈÈÈ¨& bull;¨Create custom property types to extend SharePoint & rsquo;s functionality ÈÈÈ¨& bull;¨Integrate with other systems and SharePoint sites so that you can use their information more effectively ÈÈÈ¨& bull;¨Customize themes and interactive Help, one step at a time ÈÈÈ¨& bull;¨Customize email alerts and system notifications ÈÈÈ¨& bull;¨Extend the capabilities of document libraries ÈÈÈ¨& bull;¨Control document display and behavior based on extensions.